2020
DOI: 10.1016/j.marpetgeo.2020.104592
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and formation mechanism of a regional fault in shale strata: Insights from the Middle-Upper Yangtze, China

Abstract: Shale is a type of fracture-prone rock, but few regional faults are observed in shale strata. Here, we investigate a regional detachment fault in the Middle-Upper Yangtze (MUY) to understand the formation mechanism of a special regional fault in shale strata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Zhang et al studied shale gas accumulation in the syncline settings and found that shale gas escaped along the bedding is the dominant reason for the poor gas content of shale. Bedding fractures and detachment layers commonly developed at the bottom of the Longmaxi Formation are the main channels for shale gas to escape along the bedding direction. , Hence, the greater the dip angle of the formation, the less conducive to shale gas preservation, especially when the dip angle is greater than 20° . However, the Himalayan faults with a good sealing ability of the Mugan syncline can effectively block the escape channels of shale gas along the bedding direction, which is the primary reason for the difference in gas-bearing properties between the Pengshui syncline and the Mugan syncline (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al studied shale gas accumulation in the syncline settings and found that shale gas escaped along the bedding is the dominant reason for the poor gas content of shale. Bedding fractures and detachment layers commonly developed at the bottom of the Longmaxi Formation are the main channels for shale gas to escape along the bedding direction. , Hence, the greater the dip angle of the formation, the less conducive to shale gas preservation, especially when the dip angle is greater than 20° . However, the Himalayan faults with a good sealing ability of the Mugan syncline can effectively block the escape channels of shale gas along the bedding direction, which is the primary reason for the difference in gas-bearing properties between the Pengshui syncline and the Mugan syncline (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 An open fault is a direct escape channel of shale gas; subsequently, the overpressured state of the reservoir is destroyed and the reservoir space is more easily transformed by tectonic stress, which is a mutually promoting process. 27,28 Hence, fault sealing is crucial, and its quantitative evaluation has gradually received attention. The main research methods include the mudstone smearing evaluation, 29 fluid inclusion analysis, 30 and fault plane stress analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, shrinkage fractures and abnormally high-pressure fractures account for a small proportion and are mostly filled by later mineralization [22][23][24], so they have little impact on the enrichment and preservation of shale gas. However, interlayer shear fractures, bedding detachment fractures, interlayer expansion fractures, and interlayer fractures have a greater impact on gas enrichment and preservation [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%